Growing public : social spending and economic growth since the eighteenth century. - Lindert, Peter H. (Cambridge University Press, 2004)
Growing Public examines the question of whether social policies that redistribute income impose constraints on economic growth. Lindert argues that, contrary to the intuition of many economists and the ideology of many politicians, social spending has contributed to, rather than inhibited, economic growth.